Case Report: Exploring beyond tumors: intra-abdominal mass in a young patient with Crohn's disease - Daswaney, Akash; Patel, Pratikkumar; Haricharan, Ramanathapura; Mohamed, Rehab; Ahuja, Kanya (Frontiers in Pediatrics, 2025)
An abdominal mass is an uncommon manifestation of Crohn's disease, often mimicking the granulomatous, infectious, or neoplastic conditions. In this case, a 12-year-old girl presented with abdominal pain and a mass in the right lower quadrant (RLQ). Despite the absence of typical gastrointestinal symptoms, investigations revealed an indeterminate abdominal mass. Colonoscopy revealed a polypoid mass in the cecum, which eventually led to an ileocecectomy. Biopsy results showed noncaseating granulomas, characteristic of Crohn's disease (CD). Laboratory tests indicated anemia, elevated inflammation markers, and positive genetic markers for CD. This case underscores the diagnostic challenge of CD in children, particularly when it presents atypically as a benign mass. It emphasizes the importance of considering inflammatory bowel disease (IBD) in the differential diagnosis of intraluminal intra-abdominal masses and stresses the need for early recognition and treatment to improve outcomes, highlighting the significance of a comprehensive evaluation incorporating symptoms, radiology, and histological evidence.